2019
DOI: 10.1177/2055217319849721
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of clinically isolated syndrome to multiple sclerosis: a prospective multi-center study in Eastern India

Abstract: Background In White populations more than 60% of clinically isolated syndrome (CIS) convert to multiple sclerosis (MS) on a long-term follow-up; several predictors for conversion have been identified. Objective This study aimed to determine the conversion rate and the predictors of conversion from CIS to MS (McDonald 2010) among Indians. The other objective was to evaluate the diagnostic accuracy of the new McDonald 2017 criteria in prediction of a second clinical attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
(63 reference statements)
2
10
0
9
Order By: Relevance
“…That said, the 35.5% rate of con ver sion to MS found in our study could have increased if the study had as sessed a lon ger fol low-up pe riod. There is con flict ing ev i dence in the lit er a ture whether sociodemographic fac tors af fect con ver sion to MS. Accord ing to some stud ies, an early dis ease on set is re lated to a higher risk of de vel op ing MS [8,[11][12][13]. How ever, there is ev i dence that age does not af fect con ver sion to MS [7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…That said, the 35.5% rate of con ver sion to MS found in our study could have increased if the study had as sessed a lon ger fol low-up pe riod. There is con flict ing ev i dence in the lit er a ture whether sociodemographic fac tors af fect con ver sion to MS. Accord ing to some stud ies, an early dis ease on set is re lated to a higher risk of de vel op ing MS [8,[11][12][13]. How ever, there is ev i dence that age does not af fect con ver sion to MS [7].…”
Section: Discussionmentioning
confidence: 98%
“…Ac cord ing to our re sults, 35.5% of pa tients con verted to MS, and di min ished sense of vi bra tion and proprioception was sta tis ti cally more likely to oc cur in the MS group. However, dif fer ent con ver sion rates have been shown worldwide: in Brazil it was found that 87.3% of clin i cally iso lated syn drome (CIS) pa tients con verted to MS dur ing 5-year follow-up pe riod [7], 43.9% con verted in an In dian study [8], and 85.4% in Tur key [9], re spec tively. How ever, ac cord ing to the study by Liao et al, only 11% of pa tients with acute dis sem i nated encephalomyelitis (ADEM) con vert to MS dur ing lon ger fol low-up pe ri ods [10].…”
Section: Discussionmentioning
confidence: 99%
“…The latter were often referred to as optico spinal/Asian form of MS. 14,15 In hindsight, these were more likely to have been NMOSD as currently defined. Table 1 summarizes the studies [16][17][18][19][20][21][22][23][24][25][26][27][28] done since 1999 that describes clinical and demographic features of MS in India. The earlier studies published between 1999 and 2005 used Poser's criteria 29 for diagnosis, but the majority of studies employed Mc Donald 2010 30 or 2017 31 criteria.…”
Section: Demographic and Clinical Features Of Multiple Sclerosismentioning
confidence: 99%
“…Many previous studies have examined a typically narrow set of predictors of progression from a first demyelinating event to clinically definite multiple sclerosis in a wide range of populations (recent examples include other studies 6–11 ). Such studies have highlighted that older age at first demyelinating event, optic neuritis, isolated sensory symptoms, any exposure to a disease-modifying drug, and normal MRI impart a more favourable prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, first symptom location in the brainstem or the supratentorial region (compared to the optic pathways), 12 having at least one gadolinium-enhancing MRI lesion, and three or more periventricular lesions were factors associated with worse prognosis. 6 , 9 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%